Transformasi Pendidikan Multikultural di Madrasah dan Pesantren: Antara Tradisi, Moderasi, dan Inovasi - Cici Mulia Sari; Alfauzan Amin; Zubaedi; Hery Noer Aly (Institut Kariman Wirayudha Sumenep, 2026)
This study examines the dynamics of multicultural education transformation in madrasahs and pesantren, two Islamic educational institutions that have long served as pivotal spaces for shaping moral and intellectual character in Indonesia. Employing a descriptive approach through an extensive literature review, the study explores how tradition, moderation, and innovation intersect to influence the orientation and practice of multicultural education within these institutions. The findings reveal that tradition operates not merely as a normative legacy, but as an epistemological anchor that allows Islamic values to be continuously reinterpreted amid the plural realities of Indonesian society. Meanwhile, moderation constitutes a dialogical arena that nurtures inclusive and tolerant attitudes, manifested through sustained intergroup engagement, strengthened diversity literacy, and various community-based deradicalization initiatives. Innovation, on the other hand, emerges through curriculum redesign, the adoption of digital learning technologies, and more adaptive institutional governance. These findings indicate that the transformation of multicultural education in madrasahs and pesantren proceeds not in a linear fashion but through an ongoing dialectic between traditional continuity and reformist imperatives. Consequently, the study underscores that the success of such transformation depends on the institutions’ capacity to preserve their cultural roots while simultaneously embracing constructive change, thus enhancing their role in cultivating a tolerant and pluralistic society.